Strategi Pengembangan Wisata Pemandian Wae Tuo Temboe Dalam Memberdayakan Masyarakat Di Desa Bontominasa Kecamatan Bulukumpa Kabupaten Bulukumba - Ira Irnawati; Muh. Anwar; Muzdalipafah Sahib (Jurnal Berita Sosial, 2024)
This research is how the strategy of developing Wae Tuo Temboe bathing tourism empowers the community in Bontominasa Village, Bulukumpa District, Bulukumba Regency. Then it is described into several sub-problems, namely: 1) How are the efforts to develop Wae Tuo Temboe bathing tourism in empowering the community? 2) How is the development of the community's economy in Wae Tuo Temboe bathing tourism?. This type of research is qualitative research using a sociological approach. Furthermore, the data sources used are primary data and secondary data. For data collection through observation, interviews, and documentation. Then the data processing and analysis techniques are carried out through three stages, namely: data reduction stage, data presentation stage, data verification stage or drawing conclusions. The results of the study showed that efforts to develop Wae Tuo Temboe bathing tourism in empowering the community, namely: 1) the community contributed to the success of Wae Tuo Temboe bathing tourism in the form of contributions of thoughts (ideas/concepts), contributions of energy to establish facilities and promote through social media. 2) The development of the community's economy in Wae Tuo Temboe bathing tourism has increased since the establishment of this tour until now which is felt by traders and employees. The implication of this research is that cooperation is needed between the owner and the community in developing Wae Tuo Temboe bathing tourism in Bontominasa Village, Bulukumpa District, Bulukumba Regency. Wae Tuo Temboe bathing tourism has a very high selling value so that it attracts the interest of visitors and community efforts that are able to develop Wae Tuo Temboe bathing tourism and can improve the community's economy.